Convergence of Economic and Statistical Accounting and Analysis in the Social Sphere - M. A. Eskindarov; V. N. Salin; M. V. Melnik; O. E. Mikhnenko (Учёт. Анализ. Аудит, 2024)
The article opens a discussion about the role of accounting and analytical processes and statistics in the formation of information that provides the possibility of a systematic justification of management decisions and determines the directions for the effective development of economic entities at all levels, allowing to address the issues and problems of economic growth of large economic systems and solving social problems, ensuring a decent standard of living for citizens. Defining the urgent tasks of expanding and improving the quality of information support of management, the authors analyzed the evolution of accounting systems and statistics in Russia both during the centralized economy and during the formation of a market economy, in order to identify the best traditions and assess the widespread use of domestic experience, generalize and expand the best practices, rational use of foreign experience and international methodological documents. The aim of this work was to identify the best traditions, to objectively assess the use of domestic and foreign experience (including international methodological documents) and to summarize the most notable practical achievements in the field under study. The article formulates the urgent task of harmonizing the development of statistics and accounting, determining the main directions for improving the information support of the direction and management systems, and special attention is paid to the expediency of the development of corporate statistics and methodology of accounting processes in corporate structures as the most relevant direction, allowing a more complete and objective assessment of the effectiveness of the country’s economic development.